P1282BODY COMPOSITION AND VENTRICULAR FUNCTION IN HEMODIALYSIS, CLOSED COMPARTMENTS?. (6th June 2020) - Carbayo, Javier; Abad Esttebanez, Soraya; Verde, Eduardo; Muñoz de Morales, Alejandra; González-Rojas, Ángela; Acosta, Adriana; Delgado, Andrés; Sã¡nchez Cã¡mara, Luis Alberto; Vega, Almudena; Goicoechea, Marian
Abstract: Background and Aims: Right ventricular dysfunction is common among hemodialysis (HD) patients and it has been recently described as a marker of cardiovascular morbidity and mortality. Nevertheless, mechanisms responsible for have not been clearly elucidated. Volume overload, retrograde left ventricular dysfunction, pulmonary hypertension, left-right shunt and mineral bone disease have been related. Similarly, body composition and chronic fluid overload are closely linked to survival in dialysis patients. However, there are no data about correlation between body composition and echocardiographic parameters in previous studies The aim of this study was to assess the relationship between body composition and changes in right and left ventricular function in patients on maintenance hemodyalisis. Method: We conducted a retrospective and longitudinal observational cohort study over a population of 78 patients on maintenance hemodyalisis at a single hospital. They were on chronic hemodyalisis program of three weekly sessions of 240 minutes duration. A transthoracic echocardiogram (TTE) and a bioimpedance (BI) were performed in the same month, in the first inter-dialysis day of the week, being the patients asymptomatic and clinically stable, at the beginning and at the end of the study. The follow-up time since the completion of first and second ETT and BI was 19.5 months, with an average total follow-up of 29.7 months. Cardiovascular and general mortality events were recorded during that period. Echocardiography data about cardiac cavities measurement, ventricular and valvular function was collected. Left ventricular ejection fraction was evaluated by Simpson's method (LVEF, %) and right ventricular function by tricuspid annular plane systolic excursion (TAPSE, mm).We gathered information about fluid status and corporal composition. Statistical analysis was performed using SPSS Statistics, version 21 (SPSS, Inc., Chicago, IL, USA). Results: Patients with RV dysfunction (35.7%), determined as TAPSE < 20, experienced a higher mortality rate (20%) compared to those who maintained TAPSE ≥ 20 (63.2%), who had a mortality rate of 2.3%. These results were statistically significant in the Kaplan-Meier survival analysis (Log Rank 6.65; p = 0.010). There were not statistically significant differences regarding age, diabetes, years on dialysis and status of volume overload between patients with and without right ventricular dysfunction. No significant differences were found between any other of the echocardiography parameters and overall mortality. Equally, neither bioimpedance measure at the beginning of the study was associated with mortality. Patients who had an FTI above the average (9.20 kg / m2) suffered a greater fall in TAPSE (-1 ± 4.3 mm) (p = 0.032) and LVEF (-4.2 ± 6.8) (p = 0.045), regarding those with lower FTI: TAPSE +2.3 ± 4.3 and LVEF +3.7± 10.4. These results seems to be related to a disproportionate LTI/LTI index rather than a greater total mass of fat due to patients with FTI > 9.2 kg/m2 had a mean LTI/FTI index of 1.1, meanwhile those with FTI < 9.2 kg/m2 a mean LTI/FTI of 5.9. No statistically significant relationship was found with absolute or relative volume overload, nor with changes in them over time. Conclusion: The results presented suggest that high fat tissue index, and an underlying lower LTI/FTI index, could be associated with a higher risk of right and left ventricular dysfunction, which has been associated with higher mortality in hemodialysis patients.